PENETAPAN TAKWIM HIJRIAH MENURUT SAADOEâDDIN DJAMBEK - Hasan, Muhammad (LP2M IAIN Mataram, 2010)
Saadoeâddin Djambek is one of the leading figures in the field of Islamic astronomy (Falak) in Indonesia. His thoughts scatter in many manuscripts. Djambekâs work has been influenced by medieval Muslim scholars in astronomy and this intellectual process greatly affects his thoughts. This study aims to describe Saadoeâddin Djambekâs concept of takwim in Islamic lunar calendar (Hijriah). This research reveals that Saadoeâddin has built his concepts of the beginning of Hijriah month on the holy Qurâan combined with modern astronomical calculation. He makes use of modern principles in astronomy to sustain his system of calculation of the lunar calendar. Whereas, the Quran and Hadith constitute his epistemological foundation. This method results the concept of calculating the beginning of new moon and the alteration of Hijriah month, the beginning of day and date of Hijriah called wujÃ»d alhilÃ¢l. In his concept of takwim, he offers a solution to the problem regarding different calculation of the beginning of Hijriah month in a particular region. The concept of determining the beginning of the month and the takwim of Hijriah have strong epistemological foundation that result accuracy calculation. He also uses to some degree the principle of the unity of Muslim community (ukhuwah) in his calculation method and this helps reduce friction in determining the beginning of Islamic lunar calendar amongst Muslims.